PERLINDUNGAN HAK CIPTA TERHADAP SKETSA DAN PATUNG “TUGU SELAMAT DATANG” BERDASARKAN UUHC - Yunita Afianti; Irene Rakhmita Desmayanti (Fakultas Hukum Universitas Trisakti, 2021)
Decision Number 35/Pdt.Sus-Copyright/2020/PN Niaga Jkt.Pst is a lawsuit for compensation due to the use and registration of the Grand Indonesia Mall Logo mark which is in the form of a silhouette like a sketch/welcome monument statue. The problem in this material is how to protect the copyright for the welcome monument sketch and statue based on Law Number 28 of 2014 concerning Copyright, and whether Decision Number 35/Pdt.Sus-Copyright/2020/PN Niaga Jkt.Pst is appropriate with statutory regulations. The research method is descriptive analysis, through literature studies and interviews to understand, the data is analyzed qualitatively, by drawing conclusions with a deductive mindset. The conclusions that can be drawn are Article 34 and its explanation and Article 35 along with the explanation of Article 35 paragraph (1) of the Copyright Law which regulates the existence of copyright protection due to a work/official relationship made under the leadership of the designer of the work, therefore the sketch and statue of the welcome monument protected by the Copyright Act, and Decision Number 35/Pdt.Sus-Copyright/2020/PN Niaga Jkt.Pst not in accordance with statutory regulations because the sketch and statue of the welcome monument were made in the context of official relations.